In-situ formation of solidified hydrogen thin-membrane targets using a pulse tube cryocooler. (April 2016) - Astbury, S; Bedacht, S; Brummitt, P; Carroll, D; Clarke, R; Crisp, S; Hernandez-Gomez, C; Holligan, P; Hook, S; Merchan, J S; Neely, D; Ortner, A; et al.
Abstract: An account is given of the Central Laser Facility's work to produce a cryogenic hydrogen targetry system using a pulse tube cryocooler. Due to the increasing demand for low Z thin laser targets, CLF (in collaboration with TUD) have been developing a system which allows the production of solid hydrogen membranes by engineering a design which can achieve this remotely; enabling the gas injection, condensation and solidification of hydrogen without compromising the vacuum of the target chamber. A dynamic sealing mechanism was integrated which allows targets to be grown and then remotely exposed to open vacuum for laser interaction. Further research was conducted on the survivability of the cryogenic targets which concluded that a warm gas effect causes temperature spiking when exposing the solidified hydrogen to the outer vacuum. This effect was shown to be mitigated by improving the pumping capacity of the environment and reducing the minimum temperature obtainable on the target mount. This was achieved by developing a two-stage radiation shield encased with superinsulating blanketing; reducing the base temperature from 14 ± 0.5 K to 7.2 ± 0.2 K about the coldhead as well as improving temperature control stability following the installation of a high-performance temperature controller and sensor apparatus. The system was delivered experimentally and in July 2014 the first laser shots were taken upon hydrogen targets in the Vulcan TAP facility.